VD_FINDINFO PC 4/15 - 5/2016 vom 3. März 2016 - VD Tribunal cantonal (2016)
PC, FORTUNE PRISE EN CONSIDÉRATION, REVENU DÉTERMINANT | 11 al. 1 let. c LPC, 11 al. 1 LPC, 9 LPC, 17 al. 1 OPC-AVS/AI, 17 al. 4 OPC-AVS/AI